+0  
 
0
423
3
avatar

((e^x-e^(-x))/2)^2-1

math algebra
Guest Aug 23, 2014

Best Answer 

 #2
avatar+20001 
+10

((e^x-e^(-x))/2)^2-1

$$\left(
\dfrac{e^x-e^{-x}}{2}
\right) ^2
-1
=\sinh^2{x}-1 = \cosh^2{x}-2
=
\left(
\dfrac{e^x+e^{-x}}{2}
\right) ^2
-2
\\\\
( \cosh^2{x}-\sinh^2{x} =1 )$$

heureka  Aug 25, 2014
 #1
avatar+93301 
+5

 

 

$$\left( \frac{e^x-e^{-x}}{2}\right)^2-1\\\\
= \frac{(e^x-e^{-x})^2}{2^2}-1\\\\
= \frac{e^{2x}-2e^xe^{-x}+e^{-2x}}{4}-\frac{4}{4}\\\\
= \frac{e^{2x}-2+e^{-2x}}{4}-\frac{4}{4}\\\\
= \frac{e^{2x}+e^{-2x}-6}{4}\\\\
\mbox{Do you want me to keep going? It is probably finish now:)}\\\\
= \frac{e^{2x}+\frac{1}{e^{2x}}-6}{4}\\\\
= \frac{\frac{e^{4x}+1-6e^{2x}}{e^{2x}}}{4}\\\\
= \frac{e^{4x}+1-6e^{2x}}{4e^{2x}}\\\\
= \frac{e^{4x}-6e^{2x}+1}{4e^{2x}}\\\\$$

Melody  Aug 24, 2014
 #2
avatar+20001 
+10
Best Answer

((e^x-e^(-x))/2)^2-1

$$\left(
\dfrac{e^x-e^{-x}}{2}
\right) ^2
-1
=\sinh^2{x}-1 = \cosh^2{x}-2
=
\left(
\dfrac{e^x+e^{-x}}{2}
\right) ^2
-2
\\\\
( \cosh^2{x}-\sinh^2{x} =1 )$$

heureka  Aug 25, 2014
 #3
avatar+93301 
0

Thanks Heureka,

I had forgotten about cosh and sinh    

Melody  Aug 25, 2014

4 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.